Gendered Trade Governance during Covid-19 - Roberts, Adrienne; Trommer, Silke (Revue Interventions économiques / Papers in Political Economy, 2026)
The scholarship on trade linkages investigates how trade policy interacts with other policy spheres, such as security, environment, labor or human rights. Recently, this literature has turned towards examining the politics of what is considered to lie “inside” and “outside” of the trade governance arena. Our article offers an engagement with such questions of “trade linkages vs. trade disconnects” from a feminist political economy perspective. We critically analyze the linkages and disconnects between trade and gender, and trade and social reproduction, which is integrally related to the former, in the global trade policy response to the Covid-19 pandemic. We find that global trade policy-makers acknowledged the link between trade and gender during the Covid-19 pandemic and recognized how Covid-19 revealed the insecurities associated with women’s position in productive and reproductive labor. At the same time, our analysis reveals that the Covid-19 trade response also reproduced gender based-inequalities in global trade governance, including the false distinction between production and social reproduction, the privileging of the former above the latter, and the lack of challenges to existing trade rules or orthodoxies, which themselves fuel gender-based inequalities and crises in social reproduction. Overall, we conclude that long-standing disembeddedness and exclusions can be reproduced in the making of new trade linkages, unless the power relations that underpin global trade and global trade governance are actively identified and disturbed.